CONFIGURATION OF Co PHASE AND MAGNETORESISTANCE PROPERTIES IN HIGH ENERGYMILLED Co-CGRANULAR COMPOUNDS - S. Purwanto; E. Sukirman (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2017)
CONFIGURATION OF Co PHASE AND MAGNETORESISTANCE PROPERTIES IN HIGH ENERGYMILLED Co-CGRANULAR COMPOUNDS. The Co-C granular compounds which composition of Co: C was 36:34 prepared using high energy milling (HEM) process for 4.5, 12 and 20 h. The samples were characterized using X-RayDiffraction with CuKα radiation. Subsequently, the magnetic hysteresis loop of the samples was measured by a Vibrating Sample Magnetometer (VSM). Themagnetoresistance (MR)wasmeasured by standar Four Point Probe (FPP). The of XRD analyses show that a-Carbon, Co-HCP and C-FCC phases existed for the samples of 4.5 and 12 hours milling. Furthermore, the magnoresistance curves show positive trend for the samples. On the other hand, Co3O4 phase beside of C, Co-HCP, Co-FCC phases existed with negative trend for magnoresistance curve for the samples of 20 hours milling.